(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines a comprehensive framework for preventing violence in both school and digital settings. Faculty members of the Department of Psychology at Fergana State University designed and validated a questionnaire for detecting incidents of violence in schools. Based on the survey results—and in partnership with the “Contribution to the Future” Charitable Foundation and UNESCO’s Institute for Information Technologies in Education (UNESCO IITE)—a practice-oriented course was developed for teachers, psychologists, and students. The course integrates international best practices and recent legislative acts of the Republic of Uzbekistan in the fields of child protection, education, and cybersecurity.